2011
DOI: 10.1001/archoto.2011.184
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Laryngeal Electromyography in Children With Vocal Fold Immobility<subtitle>Results of a Multicenter Longitudinal Study</subtitle>

Abstract: Intraoperative LEMG is a safe, easy-to-use method for determining the likelihood of recurrent laryngeal nerve function return in children who have undergone patent ductus arteriosus ligation, in children with centrally correctable lesions, and in children with idiopathic VFI. More work is needed in the area of pediatric LEMG, but it is possible that LEMG data can be used to aid in management strategies and provide families with more information to make better informed decisions regarding their child's care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 30 publications
0
21
0
1
Order By: Relevance
“…Additional techniques for vocal fold function assessment may include extubation followed by direct laryngoscopy and rigid bronchoscopy, laryngeal electromyography, or laryngeal ultrasound. Maturo et al 39 prospectively showed that laryngeal electromyography could predict recurrent laryngeal nerve function return when compared with diagnosis by flexible fiberoptic laryngeal examination. The authors reported this technique to be a safe, operator-friendly method for determining the likelihood of function return in a variety of patients, including those who had undergone PDA ligation.…”
Section: Methods Of Vocal Fold Assessmentmentioning
confidence: 99%
“…Additional techniques for vocal fold function assessment may include extubation followed by direct laryngoscopy and rigid bronchoscopy, laryngeal electromyography, or laryngeal ultrasound. Maturo et al 39 prospectively showed that laryngeal electromyography could predict recurrent laryngeal nerve function return when compared with diagnosis by flexible fiberoptic laryngeal examination. The authors reported this technique to be a safe, operator-friendly method for determining the likelihood of function return in a variety of patients, including those who had undergone PDA ligation.…”
Section: Methods Of Vocal Fold Assessmentmentioning
confidence: 99%
“…Eighteen articles reported adult or mixed adult and pediatric population without a separate analysis [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66]. Sixteen articles had flaws that disqualified them from inclusion (sampling, diagnostic definition, incomplete follow up, and non-objective assessment of final outcome) [2,4,[6][7][8]14,[67][68][69][70][71][72][73][74][75][76]. Twenty-one articles were assessing glottic expansion procedures on highly selected groups [9,[77][78][79][80][81][82][83][84][85][86][87][88][89][90]…”
Section: Electronic Search and Study Selectionmentioning
confidence: 99%
“…On reviewing the titles and abstracts produced, only 8 articles were found suitable to evaluate. 3,[6][7][8][9][10][11][12] We reviewed these references critically with respect to sample size, study design, technique, muscles sampled, use of a scale/grading for the findings, diagnoses assessed, conditions of anesthesia, and whether serial measurements took place ( Table 5). We will comment on one of these studies 9 separately because the conditions of the experiment were very different.…”
Section: Commentmentioning
confidence: 99%
“…Regarding the specific anesthesia protocol, the latest 3 studies (by Scott et al, 3 Jacobs and Finkel, 8 and Maturo et al 12 ) abandoned the previously used inhalational technique, which potentially can affect laryngeal movement, and used intravenous agents, allowing better control of the duration and depth.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation